A novel chaotic key-based algorithm for still images. (2017) - Zuo, Jinglong; Yu, Guilan
The data transmission of still images has to satisfy two objectives, namely, the limited volume reduction of the data for charging the public communication networks and the maximum safety of transmitted information. In order to satisfy the two objectives, this paper proposes a novel chaotic key-based algorithm (NCKBA). Different from recently proposed chaotic keybased algorithm (CKBA), in this algorithm, several steps were applied for enhancement: the key size was increased to 128-bits; the 1D logistic map in the original CKBA was substituted by a piecewise linear chaotic map (PWLCM) to improve the balance property of the chaotic map. Experiments are done under C++, and the results show our algorithm is efficient, secure and greatly improves the compression ratio of the image while maintaining the performance of the encryption algorithm.